Investigation of the microstructural characteristics and the tensile strength of silkworm cocoons using X-ray micro computed tomography. (1st February 2021) - Song, Wenfang; Zhang, Chengjiao; Wang, Zhaoli
Abstract: Understanding the internal microstructure of silkworm cocoons is beneficial for developing biomaterials. In this study, both domesticated ( Bombyx mori ) and wild silkworm cocoons ( Antheraea pernyi and Antheraea mylitta ) were studied using the X-ray micro computed tomography (XCT), and their microstructural characteristics were analyzed quantitatively. It is discovered that fiber widths of the cocoons significantly increased from the inner to the outer layer. It is also detected that for the three cocoons in the core regions, unaffected by the surface condition, from the inner to the outer layer, fiber percentages show significant decrease initially, and then no obvious change, and the fibers in different layers are more aligned towards the short diameter of the cocoon, and Antheraea mylitta fibers display the highest fiber orientation. Fractal dimension of the domestic cocoon was significantly reduced, whereas those of the wild cocoons display no obvious change. The two wild cocoons show significantly higher maximum strength, initial modulus and breaking energy than the domesticated cocoons, and Antheraea pernyi performs better maximum strength and breaking energy than Antheraea mylitta . The tensile property is closely related to fiber percentage, fiber intersectional density and fractal dimension. Graphical abstract: Unlabelled Image Highlights: The internal microstructure characteristics of both domesticated and wild silkworm cocoons were firstly studied using the X-ray micro computed tomography (XCT). It is detected that fiber percentages in the core regions, unaffected by the surface condition, show significant decrease initially, and then no obvious change from the inner to the outer layer. Fractal dimension of the domestic cocoon was significantly reduced, whereas those of the wild cocoons display no obvious change from the inner to the outer layer. The two wild cocoons show significantly higher maximum strength, initial modulus and breaking energy than the domesticated cocoon, attributing to their higher fiber percentages, higher fiber intersectional densities and fractal dimensions.